Length of Stay Comparison between Rivaroxaban and Warfarin in the Treatment of Pulmonary Embolism: Results from a Real-World Observational Cohort Study. (31st December 2015) - Roberts, Kirsten M.; Knight, Tamara B.; Padilla-Tolentino, Eimeira; Murthy, Manasa; Peterson, Evan J.
Abstract : Background . Trials have shown that novel oral anticoagulants may decrease length of stay versus warfarin. A comparison of length of stay in the treatment of pulmonary embolism (PE) has not been performed outside post hoc analysis of a large clinical trial. Objective . To evaluate if rivaroxaban decreases length of stay compared to warfarin plus enoxaparin in the treatment of PE. Methods . This was a multicenter, retrospective, observational cohort study. Patients were identified based on discharge diagnosis of PE and were excluded if they received anticoagulants prior to admission and had additional indications for anticoagulation or reduced creatinine clearance. The primary endpoint was length of stay. Secondary endpoints included time from initial dose of oral anticoagulant to discharge and length of stay comparison between subgroups. Results . Inclusion criterion was met by 158 patients (82 warfarin, 76 rivaroxaban). The median length of stay was 4.5 days (interquartile range [IQR], 2.7, 5.9) in the warfarin group and 1.8 days (IQR, 1.2, 3.7) in the rivaroxaban group (P < 0.001 ). Time interval from first dose of oral anticoagulant to discharge was shorter with rivaroxaban (P < 0.001 ). Conclusions . Patients given rivaroxaban had decreased length of stay versus those given warfarin plus enoxaparin for the treatment of PE.